Characteristics of Vinegar from Black Sticky Rice Tapai with Different Cooking Methods - Sari, Wiwit Juita; Asben, Alfi; Novelina (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2023)
This study aims to (i) determine differences in the cooking method of steaming and cooking method of boiling on the characteristics of vinegar from black sticky rice tapai, (ii) to determine the antioxidant and anthocyanin activity of vinegar from black sticky rice tapai using the steaming method and cooking method of boiling, (iii), to determine the cooking technique that produces the best product based on organoleptic testing and also to find out the results of consumer acceptance tests on vinegar from the best black sticky rice tapai with commercial products. The treatment in this study was the black sticky rice cooking technique by steaming and boiling. The data obtained were analyzed using paired t-test. The results showed that the use of the steaming method and the boiling method had a significant effect (P<0.05) on several characteristics of the vinegar produced from black sticky rice tapai, such as acetic acid content, alcohol content, sugar content, anthocyanin content, pH, and antioxidant activity. The total anthocyanins produced in vinegar from black sticky rice tapai using the steaming method were 20.22% and 20.14% for the boiling method, and the antioxidant activity of vinegar from black sticky rice tapai using the steaming method was 92.52% and 92.11% for the boiling method. Based on the organoleptic test, the best product obtained from the highest average preference of panelists for vinegar from black sticky rice tapai was the boiling method with parameters of color, aroma, and taste. Furthermore, in the consumer acceptance test, vinegar from black sticky rice tapai had a higher average preference value compared to commercial products with each parameter, such as color (4.04), aroma (3.92), and taste (3.88).